Lightweight AES Algorithm for Internet of Things: An Energy Consumption Analysis - Vaz, Yuri Silva; Mattos, Júlio C. B.; Soares, Rafael Iankowski (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2024: Anais do XIV Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2024)
The security of IoT applications remains one of the biggest challenges, given that the vast majority of applications are developed on devices with limited computational resources and interconnected by the Internet. By 2027, the number of active IoT applications is expected to reach approximately 30 billion, with a massive amount of data being transmitted over the Internet. Therefore, this information must be protected, as a vulnerable IoT application can lead to serious issues such as data leaks and manipulations. Thus, classical cryptographic algorithms become highly costly or even unfeasible. Optimized AES algorithms are found in the literature to provide lightweight cryptography, but none evaluate energy consumption. Faced with the challenge of implementing secure IoT applications while consuming the least energy possible, this work extends the evaluation of our previously proposed lightweight AES, assessing the energy consumption of the optimizations made in both the SubBytes and MixColumns stages. With the implemented optimizations, it was possible to achieve a reduction in energy consumption of 63.87% and 70.86% on the ESP32 and Raspberry Pi Pico platforms, respectively, when compared to the original version of the AES algorithm, making this version more viable for protecting IoT applications.